The plasma dynamic synthesis of aluminum nitride in system with gaseous and solid precursors; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Shanenkov I. I. Ivan Igorevich; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkova Yu. L. Yuliya Leonidovna (Materials and technologies new generations, 2015)
Title screen